Menalar Dinamika Konflik Wisata Goa Pindul - Laode Machdani Afala (Journal of Governance, 2017)
This paper intends to provide an overview of how the drama of the conflict took place in the tourist area of Goa Pindul, Gunungkidul egency. Through the contentious politics approach, this paper oncludes that the dynamics of conflict that occurred in the cinde tour of Pindul have increased escalation of conflict along with the development of Goa Pindul tourism that increasingly famous and bring huge profits. This happens because of the conflictual relationship between the actors, namely the government, Pokdarwis, and local communities in the management of Goa Pindul tourist attraction. The conflict was mainly triggered by the presence of an open opportunity structure of economic structure and land ownership that emerged along with the presence of Goa Pindul tourist attraction. The conflict then expanded and involved many actors through the emergence of claims in their bid for rights over the management of the tourist area.